2021
DOI: 10.3390/diagnostics11061017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Delayed Surgical Debridement in the Management of Open Tibial Fractures: A Systematic Review and Meta-Analysis

Abstract: Introduction: Open tibial fractures are complex injuries with variable outcomes that significantly impact patients’ lives. Surgical debridement is paramount in preventing detrimental complications such as infection and non-union; however, the exact timing of debridement remains a topic of great controversy. The aim of this study is to evaluate the association between timing of surgical debridement and outcomes such as infection and non-union in open tibial fractures. Materials and Methods: We performed a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…However, in our research, injury to debridement time greater than 6 hours, or even greater than 12 hours, was not shown to be a risk factor in either the bivariate or multivariate analyses. A recent systematic review and meta-analysis reported debridement time even up to 24 hours did not affect the infection rate; furthermore, it was found that competent debridement was preferred over rapid and poor debridement [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our research, injury to debridement time greater than 6 hours, or even greater than 12 hours, was not shown to be a risk factor in either the bivariate or multivariate analyses. A recent systematic review and meta-analysis reported debridement time even up to 24 hours did not affect the infection rate; furthermore, it was found that competent debridement was preferred over rapid and poor debridement [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nicolaides et al's systemic review, which included 20 studies with 10,032 open tibial fractures and similarly didn't find any statistically significant association between delayed debridement and infection rate or non-union rate[26].A comparison of the outcomes of GA IIIB open fractures of historical studies from available literature with the current study is given in Table8.…”
mentioning
confidence: 71%
“…It’s obvious that this result cannot be used to advocate for delayed debridement, but it can guide us to understand the higher relevance of Getting It Right First Time (GIRFT) and prioritising the availability of surgical expertise, skilled staff, and equipment over rushing the patient to the theatre for a rapid operation aiming to adhere to these time thresholds. This was also recommended by Nicolaides et al's systemic review, which included 20 studies with 10,032 open tibial fractures and similarly didn’t find any statistically significant association between delayed debridement and infection rate or non-union rate [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of BPS/IC is multifactorial, and the condition often presents with various comorbidities, such as pelvic organ inflammation, vulvodynia, and pelvic floor myofascial pain, which have been reported to be highly prevalent [3][4][5][6]. Furthermore, inflammation in the BPS/IC may extend to other pelvic organs, potentially contributing 1 to the complex symptomatology of this condition [7,8]. Among these comorbidities, vulvodynia has gained attention in recent years.…”
Section: Introductionmentioning
confidence: 99%